Comparative histochemical and morphometric analysis of muscle fibers of the psoas muscle in individuals of both genders with ageing - Antić Vladimir; Stojiljković Nenad; Antić Milorad (Vojnosanitetski Pregled)
Background/Aim. There is a reduction of the psoas muscle with aging, and histopathological analysis (HPA) on postmortem material also shows its significant changes with advancing age. The aim of this study was to determine the presence and distribution of types I and II muscle fibers in the human psoas muscle in individuals of different ages and genders. Methods. The material consisted of tissue samples of the right iliopsoas muscle taken from 30 adult cadavers (18 males and 12 females), aged from 30 to 90 years, divided into three age groups. The material was obtained from the Institute of Forensic Medicine, Faculty of Medicine, University of Niš, Serbia. Hematoxylin and eosin (H&E) staining was used in the H PA of muscle cells. Results. The values of astereological parameters (area, perimeter, and Feret's diameter) of type I and type II muscle fibers were greater in male cases in comparison with female ones, although with no statistically significant difference. Based on the histochemical and morphometric analysis, it was concluded that, after 70 years of life, a loss of type II muscle fibers occurred, which was more conspicuous in female cases. Conclusion. During aging, the loss of type II muscle fibers, as well as the atrophy of type I and type II muscle fibers, demonstrate similar dynamics in both genders.